Pemberdayaan Potensi Desa Wisata River Walk Di Desa Papasan Kecamatan Bangsri Kabupaten Jepara - ZAHROTUN NAFISAH (LP2M Universitas Jember, 2019)
Abstract This activity of community service based on PKM is aimed at empowering Papasan village which has the potential to become a tourism village with local wisdom and has sufficient natural resources. However, unfortunately the Jepara Regency Government is still minimal to expose the local wealth owned by each village in Jepara which should be able to become its own foreign exchange for regional management. This activity was carried out with local village government partners to identify and develop village potential with young people who are members of Karang Taruna with help of some village communities others. The Asset Based Community Development (ABCD) method is used to strive for tourism innovation of existing village assets/potential to improve people’s live. Through the following activity stages; identifying village potential, creating a Pesona Papasan River Walk tourism icon accompanied by sowing fish seeds for fishing areas, and promoting tourism village in the mass media and other media. With some these activities, Papasan village will become one of the new tourist village destination that will be visited by tourist and can improve the standard of living of the local community.